Pendekatan Metode Kolaboratif dalam Pembelajaran Kimia - Elisabeth Rukmini (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
The purpose of the study is to describe the application of collaborative learning to the teaching of undergraduate introduction to organic chemistry for the first semester of medical students at the Faculty of Medicine, Atma Jaya Catholic University. It would be presented an overview of jigsaw and fish bowling methods, as collaborative approach, those can be done in a large class (more than 50 students). Sources for teaching were created on context-based material, which has been developed to teach the aspects of bonding in carbon catenation, functional groups, polymerization and simple alkaloids.